Neurodevelopmental disorder–linked Argonaute mutations permit delayed RISC formation and unusual shortening of miRNAs by 3′→5′ trimming - Andrew Savidge; Huaqun Zhang; Vishal Annasaheb Adhav; Audrey C. Kehling; GeunYoung Sim; Zhangfei Shen; Tian-Min Fu; Kotaro Nakanishi (Proceedings of the National Academy of Sciences, 2025)
Mutations in Argonaute proteins (AGOs) cause Argonaute syndrome, a neurodevelopmental disorder (NDD), yet the underlying molecular mechanism remains unclear. We determined cryo-electron microscopy (cryo-EM) structures of wild-type (WT) AGO1 and the recurrent, severe causative ΔF180 mutant. AGO1(ΔF180) unexpectedly rearranges the hydrophobic core of the L1 domain to preserve the overall RNA-induced silencing complexes (RISC) architecture and recognize guide RNAs similarly to WT. Functionally, the mutant binds target RNAs like WT but more frequently retains passenger strands, implicating a defect in RISC assembly. Biochemical assays of ΔF180 and L190P mutants revealed normal duplex loading but impaired passenger ejection, exposing guide 3′ ends to 3′→5′ exonucleases and generating abnormally short ~11-nucleotide RNAs. In cells, AGO1(ΔF180), AGO1(G199S), and corresponding AGO2 mutants likewise produced truncated guides. Together, these findings support a model in which defective passenger ejection underlies the pathology of AGO-associated NDDs by rendering microRNAs bound to AGO syndrome mutants susceptible to aberrant 3′ trimming.